ROAD INFRASTRUCTURE AS A TOOL FOR IMPROVING INTERREGIONAL ECONOMIC INTEGRATION - A. M. Saralidze; O. A. Donichev (Финансы: теория и практика)
The paper analyzes the development of the road infrastructure since the road infrastructure is an efficient instrument for interregional economic integration. The importance of investigation into these issues consists in the fact that the road infrastructure facilities contribute to the creation of a single economic space of the federal district and the country as a whole. The relevance of topic is determined by the necessity to overcome the fragmentation in the development of the national economy and to increase the efficiency of reproductive processes. Investigations of the authors allowed to identify among all types of infrastructure the most important one for interregional cooperation - the transport and communication infrastructure and especially road transport since it is the primary means to ensure the further development of economic links and optimization of production/ marketing chain. In addition, the road transport providing passenger and freight services both within the region and between the regions is directly connected to the enhancing of the quality of living standard of the population. The study established a stable correlation between the density of roads and gross regional product per capita. Moreover, the development of the road network largely leads to higher social and economic rates in the region. Further calculations show that the suggested values of road density in regions required to achieve the desired gross regional product (GRP) per capita, significantly exceed the road density stipulated in federal policy documents on the modernization and development of roads. The obtained results clearly show that there should be a revision of state policy in the field of road construction towards an increase in normative financing according to the expected level of social and economic development of the territory.